2006
DOI: 10.1209/epl/i2006-10283-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of B and the Si/C ratio on high-temperature stability of Si–B–C–N materials

Abstract: Amorphous Si-B-C-N alloys were deposited by reactive magnetron sputtering, and their high-temperature stability was investigated using a combined approach of experiment and molecular-dynamics simulations. We show that both a higher Si/C ratio and the addition of boron improve the thermal stability of the materials. We find that lifetimes of bonds of the same type are significantly longer at the higher Si/C ratio. The addition of boron results in a conversion of some of the electrons in lone pairs associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 19 publications
(29 reference statements)
1
22
0
1
Order By: Relevance
“…2a). For the 25% N 2 + 75% Ar gas mixture, when the C content is higher (9 at.%), we obtained higher values of n and k. At V b = −100 V, higher incorporation of carbon also resulted in systematically higher values of both n and k. These changes can be correlated with the previously shown transition of the sp 3 -rich structure into a sp 2 -rich one with increasing C/Si ratio [14,35] -see also the chemical structure in Figs. 3 and 4.…”
Section: Optical Propertiessupporting
confidence: 81%
See 3 more Smart Citations
“…2a). For the 25% N 2 + 75% Ar gas mixture, when the C content is higher (9 at.%), we obtained higher values of n and k. At V b = −100 V, higher incorporation of carbon also resulted in systematically higher values of both n and k. These changes can be correlated with the previously shown transition of the sp 3 -rich structure into a sp 2 -rich one with increasing C/Si ratio [14,35] -see also the chemical structure in Figs. 3 and 4.…”
Section: Optical Propertiessupporting
confidence: 81%
“…Collectively, these data confirm the prediction of ab-initio calculations [35] that Si in such structures mainly forms single bonds, contrary to a high number of C-containing double and triple bonds. The consequently higher coordination number (lower sp 2 /sp 3 ratio) of Si-based compositions compared to Cbased systems has an important effect on the material properties such as hardness [17], thermal stability [14] or electrical conductivity [26], as well as on the tribological and optical properties discussed below. Fig.…”
Section: Elemental Composition and Bonding Structurementioning
confidence: 99%
See 2 more Smart Citations
“…To investigate the effect of boron content in the films on their oxidation resistance, the obtained results were compared to those for the Si-C-N films prepared under the same deposition conditions. 11 The ab initio simulations showed that both a higher Si/C concentration ratio in Si-͑B͒-C-N materials and the addition of boron into Si-C-N materials prevent their decomposition at elevated temperatures, resulting in formation of N 2 molecules which diffuse out of the material. As expected, 3,5 an incorporation of boron into the films resulted in their substantially higher thermal stability in air.…”
Section: Introductionmentioning
confidence: 99%